Power Moves : Transportation, Politics, and Development in Houston. - Shelton, Kyle (University of Texas Press, 2018)
Since World War II, Houston has become a burgeoning, internationally connected metropolis?and a sprawling, car-dependent city. In 1950, it possessed only one highway, the Gulf Freeway, which ran between Houston and Galveston. Today, Houston and Harris County have more than 1,200 miles of highways, and a third major loop is under construction nearly thirty miles out from the historic core. Highways have driven every aspect of Houston?s postwar development, from the physical layout of the city to the political process that has transformed both the transportation network and the balance of power between governing elites and ordinary citizens. Power Moves examines debates around the planning, construction, and use of highway and public transportation systems in Houston. Kyle Shelton shows how Houstonians helped shape the city?s growth by attending city council meetings, writing letters to the highway commission, and protesting the destruction of homes to make way for freeways, which happened in both affluent and low-income neighborhoods. He demonstrates that these assertions of what he terms "infrastructural citizenship" opened up the transportation decision-making process to meaningful input from the public and gave many previously marginalized citizens a more powerful voice in civic affairs. Power Moves also reveals the long-lasting results of choosing highway and auto-based infrastructure over other transit options and the resulting challenges that Houstonians currently face as they grapple with how best to move forward from the consequences and opportunities created by past choices.